Vägkonstruktionens påverkan av belastning och nederbörd - Karlsson,Erik (2026)
A changing precipitation pattern, characterized by shorter but more intense rainfall events, combined with increasing traffic loads, places new demands on road construction design and performance. The aim of this literature study is to investigate how road structures are affected by heavy rainfall and increased loading, as well as to analyse differences between modern and older road constructions in terms of load-bearing capacity and water management. Additionally, the study examines how current drainage solutions function in relation to these stresses. The study is based on previous research, reports, and regulatory documents from authorities such as the Swedish Transport Administration and VTI. The results indicate that modern road constructions generally perform better than older ones in handling both traffic loads and water. This is primarily due to improved design methods, stricter material requirements, and a greater consideration of site-specific conditions and climate factors. Older road constructions are often designed according to outdated standards and contain a higher proportion of fine-grained materials, resulting in poorer drainage capacity and increased sensitivity to moisture-related damage. Heavy rainfall combined with traffic loading has a clearly negative impact on road performance and lifespan. Water infiltration reduces the stiffness and bearing capacity of materials, which may lead to deformation, cracking and severe damages. These effects are further intensified by heavy traffic, particularly from overloaded vehicles, which accelerates the deterioration process. Modern drainage systems play a crucial role in maintaining road functionality and include both conventional solutions, such as ditches and slopes, and more advanced systems like permeable pavements and Blue-Green-Grey (BGG) constructions. These systems aim to efficiently remove or temporarily store water; however, their effectiveness is highly dependent on proper and continuous maintenance. Insufficient maintenance of drainage systems is identified as a major cause of flooding and structural damage. In conclusion, modern road constructions are better equipped to meet future challenges related to climate change and increasing traffic loads. Nevertheless, significant challenges remain, particularly regarding the maintenance of existing infrastructure, the impact of heavy vehicles, and the need for further development of sustainable and efficient drainage solutions.
Keywords: vägkonstruktion; dränering; nederbörd; belastning; BK4; infiltration; klimatförändringar; road construction; drainage; precipitation; traffic load; climate change